Accounting for business combinations: lessons from the U.S.A.? - Ribeiro, Humberto (2010)
The number of different accounting practices at national level is considerable in Europe. The adoption of IAS/IFRS is a relevant step towards accounting harmonization in Europe, but also results in a dual accounting system for European companies. The accounting for business combinations provides a good example of profusion of different possible methods used by companies in different European countries, with implications on the comparability of financial statements. From the twenty-one European countries surveyed by FEE in 2002, only three did not allow the pooling of interests in any circumstance. In terms of purchased goodwill accounting, amortization was the default treatment. Fifteen countries had refutable amortization period limits, but ten countries had no absolute limits. Moreover, eight countries allowed write off to equity. If the accounting for business combinations in Europe was already a Tower of Babel, another level has been then added to it following IAS/IFRS adoption by EU. Within this dual accounting system, since 2005 listed companies ruled by the law of a Member State are required to prepare their consolidated accounts according IASB’s standards (EC, 2002). The matrix of possibilities has increased. Listed companies with consolidated accounts can only use purchase method, but pooling is still allowed for the remaining, except in few countries. Purchased goodwill is to be amortized by every company, using arbitrary ceilings; or is to be written off; or, finally, is to be subject to impairment tests by companies who adopted IFRS. The discrepancy among the different national GAAP is significant, and between these and IASB’s is huge. To mitigate these differences, some European countries are preparing changes in their national sets of accounting standards. Regarding business combination accounting, countries such as the U.K. (FRED 36 – 39, 2005), and Portugal (NCRF 14, 2007), have produced exposure drafts intended to align their national GAAP with IFRS 3. However, when does such changes will be enforced is unclear. The number of countries to follow these steps is also something to be known in the next years. On the other side of the Atlantic, from 2001 the purchased method is the single accounting method accepted, and purchased goodwill is to be tested using impairment tests. A major change that included every company in the U.S.A., regardless the company status, this is, being listed or reporting consolidated statements. The adoption of the new business combinations was controversial, as many argued it would produce significant economical effects. Several managers from high tech companies even argued that M&A activity would suffer if pooling were to be abolished. To verify whether the FASB new pronouncements have had impact on the M&A activity, we have carried out a study with the purpose to capture any possible effects from the adoption of the new accounting standards. We have found that the new accounting standards did not have any significant impact on the M&A activity in the U.S.A.. Accordingly, we argue that national European accounting boards should also follow IASB GAAP to enhance comparability among European companies involved in M&A deals.